Pangsor (Ficus callosa WILLD) and kecapi (Sandoricum kucape MERR) are usually planted in garden and rural forest. The objective of this study was to determine its specific gravity (SG), maximum crushing strength (σc//), longitudinal modulus elasticity (EL), and Poisson’s ratio (n). The compression test was conducted referring to ASTM D143-94(2000) using UTM Instron 3369 which is equipped with two biaxial clip on extensometers. The result showed that vertical and horizontal position of wood i - Lusita WARDANI; Effendi Tri BAHTIAR; Ignasia Maria SULASTININGSIH; Atmawi DARWIS; Lina KARLINASARI; Naresworo NUGROHO; Surjono SURJOKUSUMO (Jurnal Ilmu dan Teknologi Hasil Hutan, 2011)
Pangsor (Ficus callosa WILLD) and kecapi (Sandoricum kucape MERR) are usually planted in garden and rural forest. The objective of this study was to determine its specific gravity (SG), maximum crushing strength (σc//), longitudinal modulus elasticity (EL), and Poisson’s ratio (n).  The compression test  was conducted referring to  ASTM D143-94(2000) using UTM Instron 3369 which is equipped with two biaxial clip on extensometers.  The result showed that vertical and horizontal position of wood in the trees statistically significant influenced on SG and σc//.  Horizontal position in Pangsor wood affected its EL, but the other position in both species were not significantly different.  There were poor correlations between SG with EL and σc//.   Poisson’s ratio value of both woods were in a range 0.0045 – 0.275 for longitudinal-radial direction (nLR), and 0.0151 – 0.1289 for longitudinal-tangensial direction (nLT).   Keywords :    Longitudinal Modulus of Elasticity, Maximum Crushing Strength, Poisson’s Ratio, Pangsor wood, Kecapi wood